(untitled)
The domain decomposition method in this paper is based on PCG (Preconditioned Conjugate Gradient method). If N is the number of subdomains, the number of sub-problems solved parallelly in a PCG step is 43(1-14^N+1 )N. The condition number of the preconditioned system does not exceed O(1+N)^3. It is completely independent of the mesh size. The number of iterations required, to decrease the energy norm of the error by a fixed factor, is proportional to O(1+N)^32 . , number=1, journal=Journal of Computational Mathematics, year=1991, month=Sept., pages=17–27